Maternal and Fetal Outcome in Eclampsia: A Study From Tertiary Care Hospital - Haque, Husneyara; Thapa, Kalpana Kumari (Journal of Nepalgunj Medical College, 2017)
Introduction: Eclampsia is an acute and life-threatening complication of pregnancy associated with elevated maternal and fetal morbidity and mortality. This study was done with the aim to evaluate the maternal and fetal outcome in eclampsia patients and to observe various factors affecting its occurrence and outcome. Methods: A retrospective cross-sectional hospital based study carried out in Nepalgunj Medical College, Nepalgunj from January 2015 to December 2016. Details and data obtained from maternity register were analysed. All patients with eclampsia were included and fetomaternal outcomes measured in terms of complications. Simple descriptive statistical method was applied for analysis. Result: Out of 6056 pregnant women, 46 had eclampsia with the incidence of 7.59 per 1000 deliveries. 58.7% of study population belonged to age group of 21-30 years followed by 36.96% from age less than 20 years. 78.26% cases were unbooked. 73.91% eclamptic patients were primi gravida and 60.87% had gestational age less than 37 weeks. Half of pregnancies with eclampsia underwent ceasarian for delivery and 30.44% required ICU care. One third women developed eclampsia related complications and 2(4.35%) died. Common complications were atonic postpartum heamorrhage (15.21%), psychosis (8.71%) acute renal failure (4.35%). 60.86% newborn were preterm and 56.52% were low birth weight. In 50% newborn, Apgar score at 5 minutes was less than 7. Fetal death was 10.85%. Conclusion: Eclampsia continues to be one of the prime etiological factors for maternal and fetal morbidity and mortality. Therefore early recognition and proper management are vital to tackle this challenge.